How to organize bidirectional tissue production? - Chiang, Min-Hao; Greb, Thomas (Current opinion in plant biology, 2019)
The cambium is a plant-borne stem cell system producing wood and bast, two distinct types of vascular tissues, in strictly opposite directions. Thereby, the cambium contributes substantially to terrestrial biomass accumulation and represents the basis for the formation of large plant bodies. Although the bidirectional mode of tissue production by a common stem cell pool holds interesting implications for developmental biology, functional domains of the cambium, and their interaction remained poorly defined for decades. Here, we summarize recent findings on domain organization of the cambium and discuss potential mechanisms important for its bipartite organization. By highlighting the conceptual implication for stem cell biology, we integrate our understanding of cambium regulation into a larger context.